2011
DOI: 10.1080/14639220903536559
|View full text |Cite
|
Sign up to set email alerts
|

An extension of the Human Factors Analysis and Classification System for use in open systems

Abstract: The Human Factors Analysis and Classification System (HFACS), based uponReason's model of human error in an organizational context is currently the most widely used human factors accident analysis framework, however it has been criticised for merely categorising accident data rather than analysing it. Previous research has established statistical associations between the levels and categories within HFACS but has not specified a mechanism by which one category influences subsequent behaviour. This paper extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…STAMP regards human errors as the symptoms of the system rather than causal factors of accidents requiring analysts to consider how system conditions may lead to "errors". STAMP provides a holistic view of human errors and organisational factors in its analysis, the human factor element of STAMP is somewhat limited and under-specified and managerial and social issues in a socio-technical system are simply viewed as sources of failure in terms of control constraints (Harris and Li, 2011). In addition, STAMP does not provide extensive guidance for understanding why humans behave the way they do (e.g., constraints covering human information processing - France, 2017) and as a result analysts have found it difficult to identify human and organisational failures (Dong, 2012;Suo, 2012;Song, 2012;Niu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…STAMP regards human errors as the symptoms of the system rather than causal factors of accidents requiring analysts to consider how system conditions may lead to "errors". STAMP provides a holistic view of human errors and organisational factors in its analysis, the human factor element of STAMP is somewhat limited and under-specified and managerial and social issues in a socio-technical system are simply viewed as sources of failure in terms of control constraints (Harris and Li, 2011). In addition, STAMP does not provide extensive guidance for understanding why humans behave the way they do (e.g., constraints covering human information processing - France, 2017) and as a result analysts have found it difficult to identify human and organisational failures (Dong, 2012;Suo, 2012;Song, 2012;Niu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Harris and Li suggested that the hybrid analytical procedure described as HFACS-X combining the features of HFACS and STAMP, produces a system with enhanced explanatory power which addresses the shortcomings of both previous systems. [19] Olsen and Shorrock [20] found that the HFACS adapted by the Australian Defence Force (ADF) was unreliable while using it to assess its suitability as incidents analysis frameworks at the air traffic control (ATC) section level. For all three studies done, the result of inter-coder consensus and intra-coder consistency was unacceptable.…”
Section: Insert Figure 2 Here ------------------------------mentioning
confidence: 99%
“…1. The Human Factors Analysis and Classification System (HFACS) framework (Wiegmann and Shappell 2003)> Some researchers have tried to extend the original HFACS framework to overcome some limitations described above (Reinach and Viale 2006;Harris and Li 2011;Chen et al 2013 Modelling System (GEMS) to define the contents of errors within 'unsafe act' level. Second, it adopted Hawkins's SHEL model to define the categories within 'precondition for unsafe acts' level.…”
Section: Hfacs (Human Factors Analysis and Classification System)mentioning
confidence: 99%